Identifying the Transport Pathways of Dissolved Organic Carbon in Contrasting Catchments. Issue 7 (24th June 2014) - Van Gaelen, Nele; Verheyen, Dries; Ronchi, Benedicta; Struyf, Eric; Govers, Gerard; Vanderborght, Jan; Diels, Jan
Abstract : Dissolved organic C (DOC) plays an important role in the cycling and distribution of energy and nutrients. However, factors controlling the transport of DOC both within and between ecosystems are not clear. The aim of this work was to identify the contributing pathways for transport of DOC to surface water in catchments contrasting in land use and hydrogeology and during different flow regimes. Stream water was sampled to observe temporal variation of DOC concentrations and quality both seasonally and at the time scale of a rain event. Major cation and silica concentrations in stream water, groundwater, soil pore water, precipitation/throughfall, and riparian zone water samples were combined in an end‐member mixing analysis to determine the contributing end‐members for DOC delivery at the catchment outlet. Results show that the change in DOC concentrations and quality observed in the stream water during a rain event can be explained by a change in contribution of the different end‐members. In the forested catchments with deep groundwater tables, the main pathway for DOC transport from the soil to the surface water during base flow was via the groundwater. Rising stream DOC concentrations during rainfall events were attributed to additional throughfall and riparian zone transport pathways. In the grassland catchments with shallow groundwater tables, DOC in the stream mainly originated from seeps. During rain events, contributions from a surficial transport pathway and riparian zone water gained importance. The importance of contributing pathways changed seasonally and highly depended on the degree of saturation of the vadose zone.